2022
DOI: 10.1021/acsomega.1c05741
|View full text |Cite
|
Sign up to set email alerts
|

Green Catalytic Method for Hydrothiolation of Allylamines: An External Electric Field

Abstract: Based on the idea of environmental friendliness, we first studied the hydrothiolation reactions of thiophenol with allylamine using a green catalystan external electric field (EEF). The hydrothiolation reactions could occur through Markovnikov addition (path M) and anti-Markovnikov addition (path AM) pathways. The calculation results demonstrated that when the EEF was oriented along F –X , F –Y , and F +Z directions, path M was accelerated. However, it is favorable for path AM only when the EEF is oriented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Indeed, subsequent STM‐BJ experiments have shown that OEEFs can accelerate other reactions, [41–47] and alternative experimental techniques with greater potential for scalability in utilizing OEEFs have been reported [48–54] . Concurrently with experimental endeavours, significant attention has been devoted to predicting and understanding the effects of OEEFs in reactivity by means of computational studies [55–76] . Remarkably, some of the pioneering computational works were reported much prior to the first experimental evidence of the impact of OEEFs in reactivity [77–81] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, subsequent STM‐BJ experiments have shown that OEEFs can accelerate other reactions, [41–47] and alternative experimental techniques with greater potential for scalability in utilizing OEEFs have been reported [48–54] . Concurrently with experimental endeavours, significant attention has been devoted to predicting and understanding the effects of OEEFs in reactivity by means of computational studies [55–76] . Remarkably, some of the pioneering computational works were reported much prior to the first experimental evidence of the impact of OEEFs in reactivity [77–81] .…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of hydrosilylation, the reaction may lead to two adducts, corresponding either to the Markovnikov addition (a-adduct) or the anti-Markovnikov addition (badduct). 9,10 What distinguishes hydrothiolation from hydrosilylation is a very low contribution (less than 5%) or no formation of a-adducts, high tolerance to various functional groups, short synthesis time and mild conditions. 11 In addition, from the application point of view, the products obtained in the hydrothiolation process have the same and sometimes even better properties (as adhesion promoters or modiers) than the analogous products obtained in the hydrosilylation process.…”
Section: Introductionmentioning
confidence: 99%